Psicanálise e cidadania em Dolto e Winnicott: os programas de rádio - Vallim, Miguel Ribeiro (2025)
This thesis investigates the relationship between psychoanalysis and citizenship in the works of psychoanalysts D.W. Winnicott and Françoise Dolto. Through documentary analysis of the radio programmes in which the two authors participated - Winnicott in the post-war UK, and Dolto in post-May 1968 France - the research identifies and compares the authors' communication and enunciation strategies, also considering the historical and social conditions of discursive production. On one hand, the analysis shows how the programmes are based on some common premises, linked to the psychoanalytic framework, reflections on the notion of citizenship and the rise of the welfare state after WWII, on the other, it shows the differences in communication strategies and the subtleties that are based on each author's own conceptions. The concept of citizenship turned out to be the central axis of the discussions around the radio programmes, both revealing the socially committed and responsible stance of these two authors and demonstrating that the care for early childhood and early relationships in general are a fundamental part of building a fair and democratic society, inhabited by citizens who deserve these title